News Credibility Perception based on Media - Siti Nahdiah; Cindy Ayu Agustin (Department of Communications, Universitas Islam Indonesia, 2017)
The developments of communication technology nowadays open up the boundaries for us to get information. We used to wait for morning newspaper or the schedule of news program on Television to get recent issues. Now we can access any kind of updated news anytime anywhere with our hands using online media. The objective of this study is to explain the credibility perception of the news from the media used by the audience in Indonesia. The focus is to determine which media is considered the most credible between print and online media. This study is based on media theory from Harold Innis, one of the first theorists in media, about the bias of communication. The positivistic paradigm and quantitative approach with survey method is used in this study. The result shows that even though nowadays online media is prefered to be used, the content of news in print media considered be more credible.Â Keywords : News Credibility; Print media; Online media